Effect of Sales Growth, Capital Structure, and Company Size on Company Value: Empirical Study of Real Estate & Property Sector Companies Listed on the Indonesia Stock Exchange - Putri, Serlya Salsabila; Lestari, Wira; Rahayu, Rahayu (PT. Riset Press International, 2023)
This study aims to determine the effect of sales growth, capital structure and company size on the Company Value of Real Estate and Property companies on the Indonesia Stock Exchange in 2017-2021. This research is a quantitative study using secondary data obtained from the company's official website and the Indonesian Stock Exchange. The population of this study were all real estate and property sector companies, totaling 83 companies. The sampling technique used purposive sampling of 38 Real Estate and Property sector companies with five years of observation and obtained 190 research sample data. The software used for data processing is IBM SPSS 25. The measurement of the Capital Structure variable in this study is measured by DER (Debt to Equiy Ratio). with sales growth. Results of this study 1) Sales growth, capital structure, and company size simultaneously affect firm value. 2) Sales Growth affects the value of the company. 3) Capital structure affects the value of the company. 4) Company size has no effect on firm value